Dynamic contrast enhanced MRI of wrist as a useful diagnostic tool in early rheumatoid arthritis - Khaled Dewan (The Egyptian Journal of Radiology and Nuclear Medicine, 2014)
Magnetic resonance imaging is the only tool, that provides the possibility of studying bone marrow edema. Aim of the work: To investigate whether DCE-MRI has a role in assessing disease activity in RA. Furthermore, if these imaging parameters could provide reliable information about destructive joint changes during follow up period. Patients and methods: 48 Patients with early RA were followed up with plain X-ray of both hands and feet with DCE-MRI of the clinically more affected wrist. Synovial inflammation was assessed by measuring E-rate. Synovial membrane hypertrophy, bone edema and erosions were scored by OMERACT at baseline and 18 months. Response to treatment was evaluated based on whether or not ⩾50% improvement was achieved. Results: Erosion score progressed while clinical and laboratory measures improved significantly from baseline to 18 months. Baseline bone edema, synovitis, pain scores, E-rate and ESR were correlated with static MRI erosion score at 18 months. Conclusion: DCE-MRI produces sensitive information regarding diagnosing and scoring synovitis (1–3) in early RA. Furthermore, it provides studying bone marrow edema which is the strongest predictor of bone erosion in early RA. Hence we conclude that DCE-MRI has a diagnostic and prognostic value in predicting bone erosion development later on.